Coins excavated in Ancient Gorgippia in the 2016 excavations - Горончаровский, Владимир; Терещенко, Андрей (Acta Archaeologica Lodziensia, 2021)
Монеты из раскопок горгиппии в 2016 г. In 2016 near the south-eastern edge of the Bosporan city Gorgippia (modern Anapa) a plot of 250 sq. m was excavated for the construction of a pool. In the course of investigations an urban district dating from the mid 4th century BC to 240 AD was opened. In it were discovered 113 coins, of which 109 proved to be identifiable. In the chronological breakdown of the material the following picture emerges: the second half of 4th century BC – 14 examples, 3rd century BC – 68 examples, 2nd century BC – 6 examples, 1st century BC – 4 examples, 1st century AD – 12 examples, 2nd century AD – 2 examples, the first half of the 3rd century AD – 3 examples. The greatest number of the lost coins can be dated to the first half of the 3rd century AD – 51 examples. The investigated plot is a usual urban area; therefore the finds adequately reflect the financial and economic situation in the polis during these periods.